HUBUNGAN ANTARA RESILIENSI DENGAN KECENDERUNGAN DEPRESI PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN - dian ayu nurmalasari; Kus Hanna Rahmi (Politeknik Kesejahteraan Sosial Bandung, 2024)
Correctional Families to be aware of mistakes, improve themselves, and not repeat criminal acts so that they can be accepted again by the community and play an active role in development. During their time in prison, inmates are isolated from the outside world, far from those closest to them, they lose their privacy and freedom, so they have to obey the rules of LAPAS which can lead to psychological pressure. This study intends to analyze the relationship between resilience With the Tendency of Depression in Prisoners in Correctional Institutions. The population in this study were convicts in correctional institutions, namely around 1914 people and then taking as many as 200 respondents who were in LAPAS were deliberately involved in this study. Respondents were selected using techniques convenience sampling, Respondents were selected based on predetermined characteristics and willingness to become respondents. This study uses a scale instrument resilience adapted from Reivich & Shatte and the depressive propensity scale instrument adapted by Schmitt. Research data were analyzed using correlational techniques Pearson’s. The results show that there is a negative relationship between resilienceand depressive tendencies. In dealing with the need for a positive response to unpleasant conditions so that they can strengthen themselves in adapting to change